Retrieval of Simultaneous Water‐Level Changes in Small Lakes With InSAR. Issue 2 (25th January 2022) - Palomino‐Ángel, S.; Vázquez, R. F.; Hampel, H.; Anaya, J. A.; Mosquera, P. V.; Lyon, S. W.; Jaramillo, F.
Abstract: Monitoring water level changes is necessary to manage, conserve and restore natural, and anthropogenic lake systems. However, the in‐situ monitoring of lake systems is unfeasible due to limitations of costs and access. Furthermore, current remote sensing methods are restricted to large lakes and low spatial resolutions. We develop a novel approach using subsequential pixel‐wise observations of the Sentinel‐1B sensor based on interferometric synthetic aperture radar to detect water level changes in small lakes. We used 24 small ungauged lakes of the Cajas Massif lake system in Ecuador for development and validation. We found Differential Interferometric Synthetic Aperture Radar (DInSAR)‐derived water level changes across lakes to be consistent with precipitation, capturing the peak of the wet seasons. Furthermore, accumulated water level changes could be explained by differences in lake area among lakes. Although with limitations, this study shows the underutilized potential of DInSAR to understand water level changes in small lakes with current radar data availability. Plain Language Summary: Lakes are essential elements of the hydrological cycle, and changes in lakes water availability affect their aquatic and terrestrial ecosystems and their associated watersheds. Monitoring water level changes is necessary to manage lake systems worldwide; however, monitoring remote and small lakes is unfeasible due to limitations of costs and access. We develop a novel approach that combines satellite remote sensing radar imagery to detect water level changes in small lakes. We used 24 small and high‐altitude unmonitored lakes in Ecuador for development and validation. We found the water level changes across lakes to be consistent with precipitation in the region. Furthermore, accumulated water level changes could be explained by differences in lake area among lakes. Our methodology underpins the underutilized potential of satellite radar observations to understand water level changes in small lakes. It also has considerable potential for the near real‐time monitoring of lake systems worldwide from space observations. Key Points: We demonstrated the utility of synthetic aperture radar interferometry to track water level changes in small ungauged lakes simultaneously Regional precipitation and area of lakes conditioned the spatiotemporal patterns of changes in water level Irregular topography and surrounding elements on the lake shores were crucial for the use of radar interferometry